Cover Feature: Untying the Photophysics of Quinolinium‐Based Molecular Knots and Links (Chem. Eur. J. 7/2020). Issue 7 (21st January 2020) - Caprice, Kenji; Aster, Alexander; Cougnon, Fabien B. L.; Kumpulainen, Tatu
Abstract : The influence of the topology of a molecule on its properties can be very subtle and difficult to assess. A comparative photophysical study was carried out on a family of closely related quinolinium‐based knots and links. The spectroscopic features of the quinolinium chromophore was used to directly visualize the effects exerted by topology on the molecular backbone. The results show that topology does affect the behavior of molecules in rather complex ways, especially when braiding is tight. More information can be found in the Full Paper by F. B. L. Cougnon, T. Kumpulainen, et al. on page 1576 .